Katalog der Mittelalterlichen Handschriften in Salzburg, Katalogband Stiftsbibliothek Mattsee, Archiv der Erzdiözese Salzburg, Salzburger Landesarchiv, Archiv der Stadt Salzburg, Salzburg Museum - Czifra, Nikolaus (Verlag der Österreichischen Akademie der Wissenschaften, 2015)
The catalogue contains manuscript descriptions of smaller collections from the county of Salzburg, especially those, held at Salzburg City Archive (Archiv der Stadt Salzburg), Salzburg District Archive (Salzburger Landesarchiv), Archive of the Archdiocese Salzburg (Archiv der Erzdiözese Salzburg), Salzburg Museum Library (Bibliothek des Salzburg Museums) as well as those held at the Library and the Archive of Mattsee Monastery. The catalogue continues a list of previous publications that make major collections of German medieval manuscripts in Salzburg accessible, such as the catalogue of German manuscripts of St. Peter, the University Library and the Latin manuscripts from Michaelbeuern Monastery.